Ukrainian peasantry and imperial autocracy in the public discourse of Right-Bank Ukraine at the beginning of the 20th century - Slozkin, Maksym (Ukrainian Peasant, 2025)
The purpose of the article: to clarify the features of the reflection of the image of imperial power in the peasant consciousness at the beginning of the 20th century, to analyze the ambivalence of this perception in the context of manipulative strategies of the autocracy. The scientific novelty of the publication lies in the fact that for the first time in historical science it clarifies the features of the perception of the image of imperial power by the Ukrainian peasantry at the beginning of the 20th century. which was characterized, on the one hand, by a loyal attitude towards the emperor, and on the other hand, by criticism of the actions of the autocracy in the context of the intractability of the land issue. Conclusions. The loyal sentiments of the Ukrainian peasantry were largely a product of Russian imperial policy, which through the Orthodox Church, education and monarchical organizations formed an illusory belief in the “good tsar” and his “fatherly care”. In reality, the declared paternalistic model of relations between the authorities and the peasants did not have any real embodiment. Growing disappointment with the autocracy’s policies led to a reorientation of peasant hopes towards the State Duma, which was seen as the only institution capable of implementing agrarian and social reforms. Its dissolution caused a wave of discontent, which deepened the social crisis in the countryside and contributed to the radicalization of the peasantry, which resulted in mass agrarian uprisings.